2016
DOI: 10.1371/journal.pone.0166662
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Glioblastoma from Brain Metastasis: Qualitative and Quantitative Analysis Using Arterial Spin Labeling MR Imaging

Abstract: PurposeTo evaluate the diagnostic performance of cerebral blood flow (CBF) by using arterial spin labeling (ASL) perfusion magnetic resonance (MR) imaging to differentiate glioblastoma (GBM) from brain metastasis.Materials and MethodsThe institutional review board of our hospital approved this retrospective study. The study population consisted of 128 consecutive patients who underwent surgical resection and were diagnosed as either GBM (n = 89) or brain metastasis (n = 39). All participants underwent preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…Glioblastoma-normalized CBF values were higher both in the enhancing tumors and in the peritumoral area of T2 signal change than those of metastatic tumors. Peritumoral CBF data provided the best discrimination between glioblastoma and metastases with an AUC of 0.54 ( p < 0.001) (Sunwoo et al, 2016). …”
Section: Differentiating Metastases From Similar-appearing Massesmentioning
confidence: 99%
“…Glioblastoma-normalized CBF values were higher both in the enhancing tumors and in the peritumoral area of T2 signal change than those of metastatic tumors. Peritumoral CBF data provided the best discrimination between glioblastoma and metastases with an AUC of 0.54 ( p < 0.001) (Sunwoo et al, 2016). …”
Section: Differentiating Metastases From Similar-appearing Massesmentioning
confidence: 99%
“…Both qualitatively and quantitatively, glioblastomas demonstrated higher intratumoral and peritumoral rCBF than metastases. They report an area under the curve (AUC) of 0.835 for differentiating the two with peritumoral rCBF (55).…”
Section: Differentiation Of Malignancy Typesmentioning
confidence: 99%
“…Several studies have reported that related cerebral blood flow (rCBF) in HGG was significantly higher than in metastasis ( P < .05), [1315] While previous reports demonstrated that rCBF values may not be sufficient for discriminating metastatic tumors from HGG. [16,17] Meta-analysis has been recognized as an effective method to answer a wide variety of clinical questions by summarizing and reviewing previously published quantitative research.…”
Section: Introductionmentioning
confidence: 99%